EXERGOECONOMIC OPTIMIZATION OF POWER SYSTEMS - Bolbot, Igor (Energy and Automation, 2015)
Substantive provisions of Exergoeconomic Optimization Method are shown here. And also Algorithms of Estimation of Power and Economic Efficiency Parameters of analysed system are represented in this work.